Perkembangan Pendidikan Islam Masa Awal Di Jawa - Sitti Muthmainnah; Bahaking Rama (Referensi Islamika: Jurnal Studi Islam, 2024)
This research aims to find out early Islamic education in Java, then find out what kind of early Islamic education institutions in Java. As well as knowing the figures of Islamic education in the early days in Java. The research method used in this research is descriptive qualitative through accurate and reliable sources in the form of journals and books. Most of the Indonesian population adheres to Islam. The entry of Islam into Indonesia cannot be separated from the da'wah campaign that helped the religion spread rapidly throughout the country. There are various hypotheses about how Islam entered Indonesia, including the beliefs of Mecca (Arabia), Gujarat (India), Persia, and China. The Islamic proselytization campaign used various means, including trade, marriage, education and culture.